Artificial Intelligence-Assisted Cytology for Detection of Cervical Intraepithelial Neoplasia or Invasive Cancer: A Multicenter, Clinical-Based, Observational Study. Issue 12 (December 2020) - Bao, Heling; Bi, Hui; Zhang, Xiaosong; Zhao, Yun; Dong, Yan; Luo, Xiping; Zhou, Deping; You, Zhixue; Wu, Yinglan; Liu, Zhaoyang; Zhang, Yuping; Liu, Juan; et al.
Abstract : (Abstracted from Gynecol Oncol 2020;159:171–178) Despite the advances of cytology-based screening for cervical cancer, its efficacy as a primary screening method in many developing countries is limited by low sensitivity for cervical intraepithelial neoplasia (CIN) or invasive cancer. Because of this, human papillomavirus (HPV) screening is often introduced for primary screening.